(untitled) (American Journal of Management, 2022)
Chief Executive Officers (CEOs) have been an important focus in strategy research for the past decade. Prior literature has explored several different CEO demographics, such as education, social ties, social capital, power, and their impact on behavior. While preceding literature has linked CEO demographics to different behavioral aspects, the focus on CEO upbringing is rather rare. Surprisingly, no research has focused on CEO childhood and its impact on corporate social responsibility. This study examines how CEO socioeconomic status (SES) during developmental years (childhood to adulthood) impacts CSR. Drawing on theory from psychology I hypothesize that firms led by CEOs with humble upbringings will invest more in CSR than other firms and that this effect is strengthened when the CEO is narcissistic. I find support for my hypotheses within a dataset of Fortune 100 firms between 2000 and 2013.